Effect of microwave power on drying kinetics, structure, color, and antioxidant activities of corncob. (6th February 2019) - Saha, Suman Kumar; Dey, Suhrita; Chakraborty, Runu
Abstract: In this study, the effect of microwave drying (MWD) at four power levels (180, 300, 600, and 900 W) on kinetics, structure, color parameters, and antioxidant activity of corncob (CCB) was evaluated. Hot air‐dried (HAD) and freeze‐dried (FD) CCBs were used as controls. Drying conditions significantly affected the physicochemical characteristics as well as bioactivities of CCB. For MWD products, direct absorption of electromagnetic energy by water molecules greatly accelerated the evaporation process, leading to a faster dehydration with a very high moisture diffusivity value. Additionally, the application of microwave markedly enhanced disintegration of cellular components manifested in lowered values of structural and color attributes for MWD CCBs, which facilitated the liberation of bound polyphenols into fractions of free phenolic compounds and intensified the ultrasound‐assisted extraction of antioxidants. The presence of rutin, protocatechuic acid, gallic acid, caffeic acid, chlorogenic acid, and quercetin was responsible for high bioactivity of MWD CCB. However, thermal‐ and oxidation‐induced degradation of thermolabile polyphenols was responsible for the loss of antioxidant activity at higher (600 and 900 W) and lower (180 W) microwave powers. CCB dried using 300 W microwave power was the best drying process with the highest content of bioavailable antioxidants and antioxidant activity. Practical applications: Using lignocellulosic plant part as a source of functional food or nutritional compounds requires intensive studies on the nutritional quality of products as well as bioavailabilities of such compounds. As most of the antioxidant compounds remain bound to cellulose and hemicellulose in seed, cob, and peel, techniques that promote the disintegration of bound polymeric complexes improve the bioactivity of these products. The present research highlights the potential benefits of microwave drying for the improvement in the bioactivity of corncob (CCB). The presence of several key phenolic compounds suggests a potential application of CCB in medicinal, cosmetic, and food industries.